2005
DOI: 10.1159/000083662
|View full text |Cite
|
Sign up to set email alerts
|

Sufficient Weight Reduction Decreases Cardiovascular Complications in Diabetic Patients with the Metabolic Syndrome

Abstract: Background: The metabolic syndrome is associated with an increased risk of cardiovascular complications. Especially patients with evident cardiac pathology are at high risk for further complications. A sufficient weight reduction would improve the metabolic pathology and reduce the cardiovascular risk. Unfortunately, overweight and obese patients, even with complicated coronary heart disease, do not alter lifestyles regarding fat intake and physical activity, and in a quarter of these patients body weight incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…Our finding of the effect of orlistat on SUA level improvement was supported by evidence from previous trials 20,21 and in the first group of one trial. 25 However, in contrast to our results, some trials revealed that orlistat is caused decrease SUA but not significantly 22,24 and in the first group of one trial. 26 Also one trial 23 and in the second group of two trials 25,26 were showed that increase SUA after orlistat therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding of the effect of orlistat on SUA level improvement was supported by evidence from previous trials 20,21 and in the first group of one trial. 25 However, in contrast to our results, some trials revealed that orlistat is caused decrease SUA but not significantly 22,24 and in the first group of one trial. 26 Also one trial 23 and in the second group of two trials 25,26 were showed that increase SUA after orlistat therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Of the 4 studies investigating sibutramine, 3 53,55,56 found that heart rate increased in patients treated with sibutramine and decreased or did not change in the control groups. Only 1 study 52 showed lowering of heart rate in the intervention and control groups, with a 49 Cocco et al, 50 more pronounced decrease in patients with sibutramine therapy.…”
Section: Results Of Data Synthesismentioning
confidence: 96%
“…Eighteen of the studies were randomized controlled trials of mainly dietary interventions . There were 30 randomized, placebo‐controlled trials of obesity drugs, including orlistat, cetilistat, sibutramine, topiramate, rimonabant, taranabant, CP‐945,598, and lorcaserin . All but one of the drug trials included the dietary advice of reduced energy intake in all treatment groups.…”
Section: Resultsmentioning
confidence: 99%